Cần Thơ có thể là đầu tàu tăng trưởng của đồng bằng sông Cửu Long? Phân tích chất lượng và lan tỏa tăng trưởng kinh tế - Phạm Khánh , Nam; Hồ Quốc , Thông; Đỗ Hữu , Luật; Trần Trung , Đức; Nguyễn Thị Tâm , Hiền; Trần Thanh , Trúc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This research analyses and evaluates the quality of growth of Can Tho city in the 2005–2018 period, comparing it with the Mekong Delta’s growth pattern. This approach allows us to determine the growth spill-over role of Can Tho to other provinces in Mekong Delta and to answer the question whether Can Tho can lead the Mekong Delta’s economic development. The results indicate that Can Tho has achieved high economic growth and had the best quality of growth in Mekong Delta. Besides, Can Tho can be in at leading role in developing Mekong Delta’s economy when it has spillover effects on the economic growth of other provinces in the area. With substantial potentials for development, Can Tho can rearrange the usage of its resources more effectively to promote the total factor production and achieve better growth.
Keywords: Economic growth; The quality of growth; Growth spill over; Can Tho; Mekong Delta